Modified Study for the Effect of Combined Cycling Loading in Plane on Dynamic Edge Crack Propagation in a Thin Plate - Mosleh, Israa Abed Alrazak; A. Alshamma, Fathi A. (Al-Khwarizmi Engineering Journal, 2024)
The significant risks associated with the occurrence of mechanical cracks in engineering applications are investigated in this paper. In particular, the specific type of crack propagation that results from mixed mode loading (modes I and II), which spreads throughout most structures, and the conditions under which it can occur are presented. Following the linear elastic fracture mechanics theory, non-proportional loading on specimens of aluminium alloy was accomplished by applying constant tensile loads in conjunction with periodic shear loads. A theoretical equation for the dynamic crack growth rate was constructed using Griffiths law for mixed mode I/II of the dynamic crack growth. This equation considers the influence of dynamic crack propagation. Experimentally, a locally designed laboratory apparatus was modified to suit the nature of the applied loads on samples with edge pre-cracks and two types of samples of aluminium alloys (AA), 6061 and 5052, at the Uni-Standard System with an edge crack length of 5 mm at mid were used. A comparison of the types of alloys used to verify the validity of the results was performed. The results showed acceptable agreement in determining crack propagation rate when predicting the results of the theoretical and experimental analyses. The results in the sample showed 5052 (0.0006, 0.000633) mm/sec for the experimental and theoretical results, respectively. In contrast, the crack propagation rate amounted to 6061 (0.000183, 0.000222) mm/sec for the experimental and theoretical results, respectively. Hence, Sample 5052 started faster and propagated cracks faster than alloy 6061.